Promotional versus (un) usual prices : evidence from Singapore - Chang, An Ting (2015)
Our study investigates deceptive pricing practices in the retail market in Singapore through the conduct of a survey and collection of data from a range of physical and online retailers. About 336 Singaporeans were surveyed to analyze perceptions on misrepresentations in prices specific to luxury items which includes fragrances, bags and watches. A significant proportion of respondents displayed little awareness of the Consumer Protection (Fair Trading) Act. Several interesting findings were also made based on the three types of pricing distortions that we focus on i.e. RRP, UP and DP Distortions. Our regression analysis for RRP Distortion revealed varying degrees of distortive pricing with factors such as frequency of purchase, type of retailer, gender, brand and retailer popularity. UP and DP Distortions were also found to be present in the pricing strategies of retailers across all 3 product categories, albeit less frequently.